How constraints affect the hunter’s decision to shoot a deer - Diekert, Florian (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Hunting is the predominant way of controlling many wildlife populations devoid of large carnivores. It subjects animals to mortality rates that far exceed natural rates and that differ markedly in which age, sex, or size classes are removed relative to those of natural predators. To explain the emerging selection pattern we develop behavioral microfoundations for a hunting model, emphasizing in particular the constraints given by the formal and informal norms, rules, and regulations that govern the hunter’s choice. We show how a shorter remaining season, competition among hunters, lower sighting probabilities, and higher costs all lead to lower reservation values, i.e., an increased likelihood of shooting a particular animal. Using a unique dataset on seen and shot deer from Norway, we test and confirm the theoretical predictions in a recreational and meat-motivated hunting system. To achieve sustainability, future wildlife management should account for this predictable selection pressure.